322 Neuroinflammatory Biomarkers for Traumatic Brain Injury Diagnosis and Prognosis: Results From the TRACK-TBI Pilot Study. (1st March 2022) - Yue, John K.; Kobeissy, Firas; Yang, Zhihui; Xu, Haiyan; Deng, Hansen; Han, Kasey; Puccio, Ava; Sun, Xiaoying; Rabinowitz, Miri; Markowitz, Amy; Okonkwo, David O.; Diaz-Arrastia, Ramon; et al.
Abstract : INTRODUCTION: The relationship between systemic inflammation and traumatic brain injury (TBI) is complex. Primary injury triggers release of pro- and anti-inflammatory cytokines, chemokines, and alarmins/alarmin response proteins. METHODS: The prospective, multicenter TRACK-TBI Pilot study was used. Subjects received head CT and blood draw within 24h of TBI. Biomarkers were extracted from plasma and included: cytokines (IL-6, IL-10, IL-15, IL-16), chemokines (monocyte chemoattractant protein 4 (MCP-4), thymus activation-regulated chemokine (TARC)), alarmin/alarmin response proteins (high mobility group box 1 (HMGB-1), serum amyloid A (SAA), c-reactive protein (CRP)), and others. Area Under the Curve (AUC) was used to evaluate marker discriminability for clinical diagnosis (TBI vs. orthopedic control (OC)/healthy control (HC)), TBI severity (GCS 3-12 vs. 13-15), radiographic injury on CT, and unfavorable vs. favorable 3- and 6-month outcome (Glasgow Outcome Scale Extended (GOSE) 1-4 vs. 5-8). Statistical significance was assessed at p<0.05. RESULTS: One-hundred sixty-eight TBI subjects, 28 OC, and 18 HCs were included. Markers associated with TBI clinical diagnosis were: IL-6, IL-10, IL-16, MCP-4, TARC, HMGB-1, SAA, CRP. Markers for TBI severity: IL-6, IL-10, IL-15, IL-16, TARC, HMGB-1, SAA, CRP. Markers for radiographic TBI: IL-6, IL-10, IL-15, IL-16, HMGB-1, SAA, CRP. Predictors (AUC > 0.70) for TBI vs. OC: HMGB-1 (AUC = 0.84), IL-16 (AUC = 0.78), TARC (AUC = 0.73). Predictors for TBI vs. HC: IL-6 (AUC = 0.92), IL-10 (AUC = 0.87), HMGB-1 (AUC = 0.87), IL-16 (AUC = 0.72). Predictors for radiographic TBI: SAA (AUC = 0.77), IL-6 (AUC = 0.76), CRP (AUC = 0.73). IL-15 predicted 3- and 6-month GOSE (AUC = 0.74/0.70, respectively). SAA predicted 6-month GOSE (AUC = 0.70). CONCLUSION: We identified a distinct profile of cytokines, chemokines and alarmin/alarmin response proteins detectable systemically within 24h of TBI. These markers may have unique importance in TBI detection, severity differentiation, and prognosis. Future research on neuroinflammatory pathways will elucidate the evolution of injury and yield potential targets for therapeutic intervention.